If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 48 = 2x + -6 Reorder the terms: 48 = -6 + 2x Solving 48 = -6 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 48 + -2x = -6 + 2x + -2x Combine like terms: 2x + -2x = 0 48 + -2x = -6 + 0 48 + -2x = -6 Add '-48' to each side of the equation. 48 + -48 + -2x = -6 + -48 Combine like terms: 48 + -48 = 0 0 + -2x = -6 + -48 -2x = -6 + -48 Combine like terms: -6 + -48 = -54 -2x = -54 Divide each side by '-2'. x = 27 Simplifying x = 27
| 1=5p-2-4p | | 4=7x | | 2(6-8x)=4(2x-3) | | -11x+22=45 | | r+0.27=-0.59 | | 6(-x-2)=48 | | r+0.27=-0.25 | | -7x+6=48 | | 2(x+1)=3(x+7)-12 | | 2x/3=6-x/4 | | 25x^2-129=0 | | 3(2+x)=2(2+x) | | x^3+10x^2+13x+24=0 | | 2(x+1)=3(x+7) | | x-2(6)=2 | | 3s^2=2s^2+1 | | 5x+4=-x-20 | | -10x-4x+13x=0-7 | | 5x-7(x-4)=51 | | 14x=(5x+14) | | y=xk | | .3.7(-83x-3)=3.7(7x-30) | | 3x+61=6x-11 | | 245-2x=43x+15 | | 5x-x=14*5 | | 6.7=-3.2+x | | 159-4x=23x+15 | | a=bc+d | | 96=5x^2-x^2 | | 41-7x=90 | | 1-5x-36x^2=0 | | 4x+1y=6 |